Perceived interpersonal sources of life satisfaction in Chinese and American students: Cultural or gender differences?. Issue 4 (4th July 2017) - Chang, Edward C.; Yang, Hongfei; Yu, Tina
Abstract: This study evaluated cultural and gender differences in perceived interpersonal sources of life satisfaction between 341 Chinese and 222 American college students. Comparative analyses indicated overall lower life satisfaction in Chinese, than in Americans. However, Chinese, compared to Americans, reported greater life satisfaction derived from perceived sources involving the self, parents, teachers and peers. Results of regression analyses indicated that, for both Chinese and Americans, the self and parents were unique sources associated with life satisfaction. However, for Americans, close friends also emerged as an additional unique source. When gender differences were examined, additional nuances were found within each cultural group. Thus, some evidence for both cultural and gender differences in perceived interpersonal sources of life satisfaction across Chinese and Americans was found. Some implications of the present findings are discussed.